Impacts of climate events on life history parameters of major commercial fishes in the Beibu Gulf, South China Sea in the last 15 years - Hong, Xiaofan; Zhang, Kui; Li, Jiajun; Xu, Youwei; Sun, Mingshuai; Jiang, Jingyuan; Xu, Shannan; Cai, Yancong; Qiu, Yongsong; Chen, Zuozhi (Frontiers in Marine Science, 2023)
A detailed understanding of the impact of climate variability on fish life histories provides a fundamental basis for the ecosystem approach to fisheries management. In this study, we evaluated the relationship between fish life-history trait parameters and climate periods, using survey data from 2006-2020 for the Beibu Gulf of the northwestern South China Sea, a fishing ground with high commercial and ecological value. We show that climate events can significantly alter the * Corresponding author.